The rebranding of Spritzer Pop / Mawaddah Mohamad - Mohamad, Mawaddah (Faculty of Art and Design, 2013)
Spritzer Pop has long been in the market and for it to be produced and manufactured by a recognized local water producer; it should have been well known throughout the country. Unfortunately, some people do not remember or even known its existence. Although it has been displayed on the shelves along the drinking aisle in the supermarket or in the fridge of a 24-hour mini mart, people seem to ignore the product. According to the observation that has been made, it gives the impression that Spritzer Pop does not have its interest point. Customers do not get attracted to the product. Even the children who are supposed to be the main target audience of Spritzer Pop prefer to have another type of carbonated fruity flavored drinks.This research is made to figure out the reason behind the issue of lack of acknowledgement among customers as well as to gather the needs of this customer in order to increase the market sale of Spritzer Pop. According to “Market Smart: The Best in Age- and Lifestyle-Specific Design”, marketers as well as designers need to follow a few simple rules when marketing to children age 3-8 and teenagers and based on the survey that has been conducted by the researcher, these children and teenagers are the major consumers of Spritzer Pop. The author of the book highlighted among the rules are to understand the specific targets and how they are having a grasp of their cognitive, emotional and social attributes and capabilities; understand how young consumers process information; and how to communicate through visuals.